2018
DOI: 10.3389/fmicb.2018.01103
|View full text |Cite
|
Sign up to set email alerts
|

Virulence Gene Sequencing Highlights Similarities and Differences in Sequences in Listeria monocytogenes Serotype 1/2a and 4b Strains of Clinical and Food Origin From 3 Different Geographic Locations

Abstract: The prfA-virulence gene cluster (pVGC) is the main pathogenicity island in Listeria monocytogenes, comprising the prfA, plcA, hly, mpl, actA, and plcB genes. In this study, the pVGC of 36 L. monocytogenes isolates with respect to different serotypes (1/2a or 4b), geographical origin (Australia, Greece or Ireland) and isolation source (food-associated or clinical) was characterized. The most conserved genes were prfA and hly, with the lowest nucleotide diversity (π) among all genes (P < 0.05), and the lowest nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 79 publications
(115 reference statements)
1
22
0
Order By: Relevance
“…The prevalence of the hylA and plcB genes in the present study was 100%. The hylA and plcB mediate the release of the bacterial cells into the cytoplasm of the host and promotes the escape of the bacteria from bound vacuoles and the surface protein actin A respectively [8]. This rate is in tune with the prevalence rate observed in the study of [3].…”
Section: Discussionmentioning
confidence: 90%
“…The prevalence of the hylA and plcB genes in the present study was 100%. The hylA and plcB mediate the release of the bacterial cells into the cytoplasm of the host and promotes the escape of the bacteria from bound vacuoles and the surface protein actin A respectively [8]. This rate is in tune with the prevalence rate observed in the study of [3].…”
Section: Discussionmentioning
confidence: 90%
“…Four Listeria pathogenicity islands (LIPI) have been verified thus far, which are involved in invasion, survival and colonization of L. monocytogenes in host tissues. LIPI-1 contains six genes including hly , prfA , plcA , plcB , mpl , and actA (Hamon and Cossart, 2011; Travier and Lecuit, 2014; Mitchell et al, 2015; Rupp et al, 2015; Wang et al, 2017a; Hadjilouka et al, 2018; Poimenidou et al, 2018). LIPI-2 encodes a series of internalin family proteins which interact with the molecular cell surface and are essential for host cell adherence and virulence (McGann et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Different strains of L. monocytogenes also exhibited high MBCs for PAA in the range of up to 0.5% [28,29,30,31]. In contrast, others concluded that PAA was able to significantly reduce L. monocytogenes from multispecies biofilms at 0.15% [32] and 0.3% [30], respectively.…”
Section: Discussionmentioning
confidence: 99%